Feldspar and quartz flotation separation collecting agent and flotation separation method

By using N,N-dimethyl-N-alkylaminopropane sulfonate and other collectors under the condition of fluorine-free weak acid, combined with the optimization of the flotation process, the separation efficiency and selectivity of feldspar and quartz are solved. The problem of insufficient results has achieved efficient and environmentally friendly separation effect between feldspar and quartz.

CN119259265APending Publication Date: 2025-01-07JIANGXI WEIHONG LITHIUM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516837.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Among the existing separation methods of feldspar and quartz, especially the fluorine-free and acid-free method, the separation efficiency and selectivity still need to be improved, and the traditional methods are harmful to the environment, making it difficult to achieve efficient separation under the conditions of fluorine-free and weak acid-free conditions.

Method used

N,N-dimethyl-N-alkylaminopropane sulfonate, sodium dodecylbenzene sulfonate, sodium alkyl polyoxyethylene ether sulfate, alkyl amine polyoxyethylene ether and fatty acid methyl ester sulfonic acid Feldspar quartz flotation separation collectors composed of salt and other combinations, and through multi-step heating, constant temperature and shear stirring and other processes, collectors with excellent selectivity and capture properties are prepared, and controlled during the flotation process. The pH value and slurry solid content achieve efficient separation of feldspar and quartz.

Benefits of technology

Under the conditions of fluorine-free weak acid, the separation efficiency between feldspar and quartz is significantly improved, the use of fluorine is avoided and the environmental harm to the environment is met, the extraction needs of high-purity quartz and feldspar is provided, and an environmentally friendly and efficient flotation separation is provided. plan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106941160000051
    Figure BDA0005106941160000051
  • Figure BDA0005106941160000061
    Figure BDA0005106941160000061
Patent Text Reader

Abstract

The invention discloses a feldspar and quartz flotation separation collecting agent and a flotation separation method. The collecting agent is prepared from the following raw materials in parts by mass: 45 to 55 parts of N, N-dimethyl-N-alkyl amino propane sulfonate, 15 to 25 parts of sodium dodecyl benzene sulfonate, 5 to 15 parts of alkyl polyoxyethylene ether sodium sulfate, 3 to 8 parts of alkylamine polyoxyethylene ether, 10 to 20 parts of fatty acid methyl ester sulfonate and 70 to 140 parts of deionized water. The collecting agent has better selectivity and higher collecting capacity under the fluoride-free weak acid condition, the separation efficiency of feldspar and quartz can be remarkably improved, meanwhile, harm to the environment due to addition of fluorine is avoided, and the collecting agent has important significance for solving the actual production problem of flotation separation of feldspar and quartz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral processing, and in particular to a feldspar quartz flotation separation collector and a flotation separation method. Background Art

[0002] Quartz and feldspar are ubiquitous in the earth's crust and are widely used in glass, ceramics, semiconductors and other fields. Pure quartz deposits are relatively rare worldwide. Quartz usually coexists with aluminum-containing silicates such as feldspar, resulting in a low SiO2 content in quartz deposits that does not meet industrial requirements. Since the surface physical and chemical properties of feldspar and quartz are similar, it is difficult to separate them. Therefore, improving the extraction and separation efficiency of feldspar and quartz is of great significance for the preparation of high-purity quartz and feldspar.

[0003] Existing feldspar and quartz separation methods include fluorine-containing acid method, fluorine-free acid method and fluorine-free acid-free method. Although the fluorine-containing acid method has a better separation effect, it is gradually being eliminated due to its toxicity and damage to the environment; the fluorine-free acid method has certain advantages in environmental protection, but its separation efficiency and selectivity still need to be improved. In order to avoid the use of fluorine, reduce the harm to the environment, and achieve good separation and extraction efficiency, it is necessary to improve the flotation separation technology. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a feldspar quartz flotation separation collector having excellent selectivity and collection performance under fluorine-free weak acid conditions, and a flotation separation method using the collector.

[0005] The invention provides a feldspar quartz flotation separation collector, which comprises the following raw materials in parts by weight: 45-55 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 15-25 parts of sodium dodecylbenzene sulfonate, 5-15 parts of alkyl polyoxyethylene ether sodium sulfate, 3-8 parts of alkylamine polyoxyethylene ether, 10-20 parts of fatty acid methyl ester sulfonate and 70-140 parts of deionized water.

[0006] The collector of the present invention is prepared by compounding N,N-dimethyl-N-alkylaminopropane sulfonate, sodium dodecylbenzene sulfonate, sodium alkyl polyoxyethylene ether sulfate, alkylamine polyoxyethylene ether, and fatty acid methyl ester sulfonate in a suitable ratio. The structure of N,N-dimethyl-N-alkylaminopropane sulfonate contains unique hydrophilic and hydrophobic groups, which can provide excellent surface activity and stability in the flotation process, and exhibits excellent selectivity in the separation process of feldspar and quartz; sodium dodecylbenzene sulfonate can effectively reduce the surface tension of the ore pulp, improve the wettability of the mineral particles, and thus improve the flotation efficiency of the mineral; the presence of sodium alkyl polyoxyethylene ether sulfate can significantly improve the wettability of the system, and enhance the dispersion of the collector. The synergistic effect of sodium dodecylbenzene sulfonate and sodium alkyl polyoxyethylene ether sulfate significantly improves the collector's ability to collect feldspar without affecting the floatability of quartz. The special molecular structure of alkylamine polyoxyethylene ether makes it have strong solubility and surface adsorption capacity in the collector system, effectively improving the collector's affinity for feldspar. Fatty acid methyl ester sulfonate can significantly reduce the foam stability during flotation, thereby optimizing the gas-liquid interface behavior during flotation. The synergistic effect of alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate can also enhance the foam's annexation ability, thereby overcoming the sensitivity and poor selectivity of traditional cationic collectors to ore slime, and further improving the flotation separation efficiency of feldspar and quartz. Through the combination of the above raw materials and their synergistic effect, better selectivity and stronger collection ability can be achieved under fluorine-free weak acid conditions, significantly improving the separation efficiency of feldspar and quartz under fluorine-free weak acid conditions.

[0007] The present invention also proposes a method for preparing the feldspar quartz flotation separation collector, comprising the following steps:

[0008] Heat and dissolve N,N-dimethyl-N-alkylaminopropane sulfonate at 35°C to 45°C, keep warm and stir for 30min to 40min, then slowly add sodium dodecylbenzene sulfonate while stirring, raise the temperature to 50°C to 55°C, keep warm and stir evenly, then add alkyl polyoxyethylene ether sodium sulfate while stirring, raise the temperature to 60°C to 65°C, keep warm and stir for at least 1h, then add alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate in sequence while stirring, cool to room temperature, stir for 30min to 40min, add deionized water to obtain the product.

[0009] The preparation method of the collector ensures the interaction between the components through multi-step heating, constant temperature, shear stirring and pH value control, which can improve the stability and effect of the collector.

[0010] The present invention also proposes a feldspar quartz flotation separation method, comprising the following steps:

[0011] S1. Screen and grade the raw ore powder, remove particles with a fineness of less than 0.074 mm, and obtain pre-treated ore powder:

[0012] S2, first adding an appropriate amount of water to the pretreated ore powder to prepare the slurry, and then adding oxalic acid until the system is weakly acidic to obtain a pretreated ore slurry;

[0013] S3, roughing the pretreated pulp, the specific steps of roughing comprising: adding the aqueous solution of the feldspar quartz flotation separation collector to the pulp, stirring evenly, and aerating flotation; the foam product obtained by roughing is the feldspar concentrate, and the tailings pulp is the quartz rough concentrate;

[0014] S4, scavenging the quartz rough concentrate 2 to 4 times, and the specific steps of each scavenging include: adding the aqueous solution of the feldspar quartz flotation separation collector to the ore pulp and stirring evenly; the foam product obtained in each scavenging is low-grade feldspar, and the tailings slurry obtained after the scavenging process is the quartz concentrate.

[0015] Preferably, in S2, oxalic acid is added to the system until the pH value is 5 to 6, which can provide the most suitable pH environment for separating feldspar and quartz using the collector, optimize the separation of feldspar and quartz, and improve the selectivity and collection of flotation.

[0016] Preferably, in S2, the solid content of the pretreated slurry is 33% to 40%. Controlling the solid content of the slurry within the above range helps to form stable foam, promote collision between mineral particles, and improve flotation separation effect.

[0017] Preferably, in S3, the dosage of the aqueous solution of the feldspar quartz flotation separation collector is 800-850 g / t slurry, and the concentration of the aqueous solution of the feldspar quartz flotation separation collector is 5-20 wt%. By controlling the dosage of the feldspar quartz flotation separation collector used in the roughing, the grade and recovery rate of the feldspar and quartz can be taken into account. If the dosage is lower than this range, the recovery rate of feldspar is reduced, and the grade of quartz concentrate is reduced. If the dosage is higher than this range, the grade of feldspar concentrate is reduced, and the recovery rate of quartz is reduced.

[0018] Preferably, in S4, the amount of the aqueous solution of the feldspar quartz flotation separation collector in each scavenging is 250-300 g / t slurry, and the concentration of the aqueous solution of the feldspar quartz flotation separation collector is 5-20 wt%. By controlling the amount of the feldspar quartz flotation separation collector used in the scavenging, the grade and recovery rate of quartz separation can be taken into account. If the amount is lower than this range, the grade of quartz concentrate is reduced, and if it is higher than this range, the recovery rate of quartz is reduced.

[0019] Preferably, in S3 and S4, the pH is controlled to be 5-6. In flotation separation, controlling the pH to be 5-6 can provide the most suitable pH environment for separating feldspar and quartz using the collector, which is beneficial to improving the separation effect of feldspar and quartz.

[0020] The beneficial effects of the present invention are as follows:

[0021] The present invention proposes a novel and highly efficient feldspar and quartz combined collector, and a feldspar and quartz flotation separation method using the combined collector under fluorine-free weak acid conditions. Compared with a single component, the composite collector has better selectivity and stronger collection capacity under fluorine-free weak acid conditions, can significantly improve the separation efficiency of feldspar and quartz, and avoid the harm of fluorine addition to the environment, providing a new and efficient solution for flotation separation and purification of feldspar and high-purity quartz. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described in detail below through specific embodiments.

[0023] In the following examples and comparative examples:

[0024] N,N-Dimethyl-N-alkylaminopropane sulfonate CAS number: 14933-08-5;

[0025] Sodium dodecylbenzenesulfonate CAS number: 25155-30-0;

[0026] Sodium alkyl polyoxyethylene ether sulfate CAS number: 9004-82-4;

[0027] Alkylamine polyoxyethylene ether CAS number: 1541-67-9;

[0028] Fatty acid methyl ester sulfonate CAS number: 93348-22-2.

[0029] Example 1

[0030] A feldspar quartz flotation separation collector comprises the following raw materials in parts by weight: 50 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 20 parts of sodium dodecylbenzene sulfonate, 10 parts of alkyl polyoxyethylene ether sodium sulfate, 5 parts of alkylamine polyoxyethylene ether, 15 parts of fatty acid methyl ester sulfonate and 100 parts of deionized water.

[0031] The preparation method of the above-mentioned collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes at a temperature of 10°C, and then sodium dodecylbenzene sulfonate is slowly added under stirring, and the temperature is raised to 50°C, and the temperature is kept and stirred evenly, and then alkyl polyoxyethylene ether sodium sulfate is added under stirring, and the temperature is raised to 60°C, and the temperature is kept and stirred for 1 hour, and then alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate are added in sequence under stirring, and the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0032] The tailings after pre-enrichment of lithium mica by flotation of a porphyritic lithium ore in Yichun were used as the raw ore powder, and the above collector was used for flotation separation of feldspar and quartz. The chemical composition of the tailings is shown in Table 1:

[0033] Table 1

[0034]

[0035] The specific flotation separation method includes the following steps:

[0036] S1. Screen and grade the raw ore powder, remove particles with a fineness of less than 0.074 mm, and obtain pre-treated ore powder:

[0037] S2. Add 400 g of pretreated ore powder to the flotation tank, first add an appropriate amount of water to the pretreated ore powder to adjust the slurry, and then add oxalic acid until the system is 5-6 to obtain a pretreated ore slurry;

[0038] S3, roughing the pretreated pulp, the specific steps of roughing include: adding 800g / t of the aqueous solution of the feldspar quartz flotation separation collector to the pulp in the flotation tank based on the weight of the pulp, stirring for 4 minutes, and aerating flotation; the foam product obtained by roughing is the feldspar concentrate, and the tailings pulp is the quartz rough concentrate; in the roughing process, the pH is controlled to be 5-6;

[0039] S4. The quartz rough concentrate is scavenged three times. The specific steps of each scavenging include: adding 300g / t of the aqueous solution of the feldspar quartz flotation separation collector to the slurry in the flotation tank based on the weight of the slurry, and stirring evenly; during the scavenging process, controlling the pH to 5-6; the foam product obtained in each scavenging is low-grade feldspar, and the tailings slurry obtained after the scavenging process is quartz concentrate.

[0040] In the above flotation separation method, the feldspar quartz flotation separation collector is prepared into a 10 wt % aqueous solution before use.

[0041] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 11.09%, which meets the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 99.41%, which meets the standard requirement for float glass industry materials (≥97%).

[0042] Example 2

[0043] A feldspar quartz flotation separation collector comprises the following raw materials in parts by weight: 55 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 25 parts of sodium dodecylbenzene sulfonate, 15 parts of alkyl polyoxyethylene ether sodium sulfate, 8 parts of alkylamine polyoxyethylene ether, 20 parts of fatty acid methyl ester sulfonate and 123 parts of deionized water.

[0044] The preparation method of the above collector is the same as that of Example 1. The prepared collector is prepared into a 10 wt % aqueous solution for standby use.

[0045] The tailings after the pre-enrichment of tantalum and niobium from the gravity separation of a tantalum-niobium ore in Yichun were used as the raw ore powder, and the above collector was used for flotation separation of feldspar and quartz. The chemical composition of the tailings is shown in Table 2:

[0046] Table 2

[0047]

[0048] The specific flotation separation method includes the following steps:

[0049] S1. Screen and grade the raw ore powder, remove particles with a fineness of less than 0.074 mm, and obtain pre-treated ore powder:

[0050] S2. Add 400 g of pretreated ore powder to the flotation tank, first add an appropriate amount of water to the pretreated ore powder to adjust the slurry, and then add oxalic acid until the system is 5-6 to obtain a pretreated ore slurry;

[0051] S3, roughing the pretreated pulp, the specific steps of roughing include: adding 850g / t of the aqueous solution of the feldspar quartz flotation separation collector to the pulp in the flotation tank based on the weight of the pulp, stirring for 4 minutes, and aerating flotation; the foam product obtained by roughing is the feldspar concentrate, and the tailings pulp is the quartz rough concentrate; in the roughing process, the pH is controlled to be 5-6;

[0052] S4. The quartz rough concentrate is scavenged three times. The specific steps of each scavenging include: adding 280g / t of the aqueous solution of the above-mentioned feldspar quartz flotation separation collector to the slurry in the flotation tank based on the weight of the slurry, and stirring evenly; during the scavenging process, controlling the pH to 5-6; the foam product obtained in each scavenging is low-grade feldspar, and the tailings slurry obtained after the scavenging process is quartz concentrate.

[0053] In the above flotation separation method, the feldspar quartz flotation separation collector is prepared into a 10 wt % aqueous solution before use.

[0054] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 11.23%, which meets the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 99.16%, which meets the standard requirement for float glass industry materials (≥97%).

[0055] Comparative Example 1

[0056] The only difference between Comparative Example 1 and Example 1 is that the collector is different.

[0057] The collector of Comparative Example 1 includes the following raw materials in parts by mass: 70 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 20 parts of sodium dodecylbenzene sulfonate, 10 parts of sodium alkyl polyoxyethylene ether sulfate, and 100 parts of deionized water.

[0058] The preparation method of the above collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes at a temperature of 100°C. Then, sodium dodecylbenzene sulfonate is slowly added under stirring, the temperature is raised to 50°C, and the mixture is stirred evenly at a temperature of 100°C. Then, sodium alkyl polyoxyethylene ether sulfate is added under stirring, the temperature is raised to 60°C, and the mixture is stirred for 1 hour at a temperature of 100°C. Then, the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0059] The remaining raw ore powder and flotation separation method are the same as in Example 1.

[0060] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 9.74%, which does not meet the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 94.56%, which does not meet the standard requirement for float glass industry materials (≥97%).

[0061] Comparative Example 2

[0062] The only difference between Comparative Example 2 and Example 1 is that the collector is different.

[0063] The collector of Comparative Example 2 includes the following raw materials in parts by mass: 50 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 30 parts of alkyl polyoxyethylene ether sodium sulfate, 5 parts of alkylamine polyoxyethylene ether, 15 parts of fatty acid methyl ester sulfonate, and 100 parts of deionized water.

[0064] The preparation method of the above collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes, and then alkyl polyoxyethylene ether sodium sulfate is added under stirring, and the temperature is raised to 60°C, and stirred for 1 hour, and then alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate are added in sequence under stirring, and the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0065] The remaining raw ore powder and flotation separation method are the same as in Example 1.

[0066] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 10.13%, which does not meet the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 95.26%, which does not meet the standard requirement for float glass industry materials (≥97%).

[0067] Comparative Example 3

[0068] The only difference between Comparative Example 3 and Example 1 is that the collector is different.

[0069] The collector of Comparative Example 3 includes the following raw materials in parts by mass: 50 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 30 parts of sodium dodecylbenzene sulfonate, 5 parts of alkylamine polyoxyethylene ether, 15 parts of fatty acid methyl ester sulfonate, and 100 parts of deionized water.

[0070] The preparation method of the above collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes, and then sodium dodecylbenzene sulfonate is added under stirring, and the temperature is raised to 50°C, and stirred for 1 hour, and then alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate are added in sequence under stirring, and the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0071] The remaining raw ore powder and flotation separation method are the same as in Example 1.

[0072] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 9.49%, which does not meet the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 95.13%, which does not meet the standard requirement for float glass industry materials (≥97%).

[0073] Comparative Example 4

[0074] The only difference between Comparative Example 4 and Example 1 is that the collector is different.

[0075] The collector of Comparative Example 4 includes the following raw materials in parts by mass: 50 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 20 parts of sodium dodecylbenzene sulfonate, 10 parts of alkyl polyoxyethylene ether sodium sulfate, 20 parts of alkylamine polyoxyethylene ether, and 100 parts of deionized water.

[0076] The preparation method of the above collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes, and then sodium dodecylbenzene sulfonate is slowly added under stirring, the temperature is raised to 50°C, and the temperature is kept and stirred evenly, and then alkyl polyoxyethylene ether sodium sulfate is added under stirring, the temperature is raised to 60°C, and the temperature is kept and stirred for 1 hour, and then alkylamine polyoxyethylene ether is added under stirring, and the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0077] The remaining raw ore powder and flotation separation method are the same as in Example 1.

[0078] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 9.61%, which does not meet the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 95.89%, which does not meet the standard requirement for float glass industry materials (≥97%).

[0079] Comparative Example 5

[0080] The only difference between Comparative Example 5 and Example 1 is that the collector is different.

[0081] The collector of Comparative Example 5 includes the following raw materials in parts by mass: 50 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 20 parts of sodium dodecylbenzene sulfonate, 10 parts of sodium alkyl polyoxyethylene ether sulfate, 20 parts of fatty acid methyl ester sulfonate, and 100 parts of deionized water.

[0082] The preparation method of the above collector is as follows: N, N-dimethyl-N-alkylaminopropane sulfonate is heated and dissolved at 40°C, and then stirred for 30 minutes, and then sodium dodecylbenzene sulfonate is slowly added under stirring, the temperature is raised to 50°C, and the temperature is kept and stirred evenly, and then alkyl polyoxyethylene ether sodium sulfate is added under stirring, the temperature is raised to 60°C, and the temperature is kept and stirred for 1 hour, and then fatty acid methyl ester sulfonate is added under stirring, and the mixture is cooled to room temperature, stirred for 30 minutes, and deionized water is added to obtain the collector. The prepared collector is prepared into a 10wt% aqueous solution for standby use.

[0083] The remaining raw ore powder and flotation separation method are the same as in Example 1.

[0084] By adopting the above-mentioned collector and carrying out flotation separation according to the above-mentioned steps, the total content of K2O and Na2O in the obtained feldspar concentrate is 9.42%, which does not meet the standard requirement for industrial preparation of ceramics (≥11%); the SiO2 content in the quartz concentrate is 94.25%, which does not meet the standard requirement for float glass industry materials (≥97%).

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A feldspar quartz flotation separation collector, characterized in that: The invention comprises the following raw materials in parts by weight: 45-55 parts of N,N-dimethyl-N-alkylaminopropane sulfonate, 15-25 parts of sodium dodecylbenzene sulfonate, 5-15 parts of alkyl polyoxyethylene ether sodium sulfate, 3-8 parts of alkylamine polyoxyethylene ether, 10-20 parts of fatty acid methyl ester sulfonate and 70-140 parts of deionized water.

2. A method for preparing a feldspar quartz flotation separation collector as claimed in claim 1, characterized in that: The steps include: Heat and dissolve N,N-dimethyl-N-alkylaminopropane sulfonate at 35°C to 45°C, keep warm and stir for 30min to 40min, then slowly add sodium dodecylbenzene sulfonate while stirring, raise the temperature to 50°C to 55°C, keep warm and stir evenly, then add alkyl polyoxyethylene ether sodium sulfate while stirring, raise the temperature to 60°C to 65°C, keep warm and stir for at least 1h, then add alkylamine polyoxyethylene ether and fatty acid methyl ester sulfonate in sequence while stirring, cool to room temperature, stir for 30min to 40min, add deionized water to obtain the product.

3. A feldspar quartz flotation separation method, characterized in that: The steps include: S1. Screen and grade the raw ore powder, remove particles with a fineness of less than 0.074 mm, and obtain pre-treated ore powder: S2, first adding an appropriate amount of water to the pretreated ore powder to prepare the slurry, and then adding oxalic acid until the system is weakly acidic to obtain a pretreated ore slurry; S3, roughing the pretreated pulp, the specific steps of roughing comprising: adding the aqueous solution of the feldspar quartz flotation separation collector according to claim 1 to the pulp, stirring evenly, and aerating flotation; the foam product obtained by roughing is the feldspar concentrate, and the tailings pulp is the quartz rough concentrate; S4. The quartz rough concentrate is scavenged 2 to 4 times, and the specific steps of each scavenging include: adding the aqueous solution of the feldspar quartz flotation separation collector according to claim 1 to the ore pulp and stirring evenly; the foam product obtained in each scavenging is low-grade feldspar, and the tailings slurry obtained after the scavenging process is quartz concentrate.

4. The feldspar quartz flotation separation collector and flotation separation method according to claim 3, characterized in that: In S2, oxalic acid is added until the pH of the system is 5-6.

5. The feldspar quartz flotation separation method according to claim 3, characterized in that: In S2, the solid content of the pretreated slurry is 33% to 40%.

6. The feldspar quartz flotation separation method according to claim 3, characterized in that: In S3, the dosage of the aqueous solution of the feldspar quartz flotation separation collector is 800-850 g / t ore pulp, and the concentration of the aqueous solution of the feldspar quartz flotation separation collector is 5-20 wt%.

7. The feldspar quartz flotation separation method according to claim 3, characterized in that: In S4, the dosage of the aqueous solution of the feldspar quartz flotation separation collector in each sweep is 250-300 g / t of ore pulp; the concentration of the aqueous solution of the feldspar quartz flotation separation collector is 5-20 wt%.

8. The feldspar quartz flotation separation method according to claim 3, characterized in that: In S3 and S4, the pH is controlled at 5-6.